Emergence of Ceftazidime-Avibactam Resistance Due to Plasmid-Borne bla(KPC-3) Mutations during Treatment of Carbapenem-Resistant Klebsiella pneumoniae Infections - Shields, Ryan K. (Antimicrob Agents Chemother, 2017)
Ceftazidime-avibactam is a novel β-lactam/β-lactamase inhibitor with activity against carbapenem-resistant Enterobacteriaceae (CRE) that produce Klebsiella pneumoniae carbapenemase (KPC). We report the first cases of ceftazidime-avibactam resistance to develop during treatment of CRE infections and identify resistance mechanisms. Ceftazidime-avibactam-resistant K. pneumoniae emerged in three patients after ceftazidime-avibactam treatment for 10 to 19 days. Whole-genome sequencing (WGS) of longitudinal ceftazidime-avibactam-susceptible and -resistant K. pneumoniae isolates was used to identify potential resistance mechanisms. WGS identified mutations in plasmid-borne bla(KPC-3), which were not present in baseline isolates. bla(KPC-3) mutations emerged independently in isolates of a novel sequence type 258 sublineage and resulted in variant KPC-3 enzymes. The mutations were validated as resistance determinants by measuring MICs of ceftazidime-avibactam and other agents following targeted gene disruption in K. pneumoniae, plasmid transfer, and bla(KPC) cloning into competent Escherichia coli. In rank order, the impact of KPC-3 variants on ceftazidime-avibactam MICs was as follows: D179Y/T243M double substitution > D179Y > V240G. Remarkably, mutations reduced meropenem MICs ≥4-fold from baseline, restoring susceptibility in K. pneumoniae from two patients. Cefepime and ceftriaxone MICs were also reduced ≥4-fold against D179Y/T243M and D179Y variant isolates, but susceptibility was not restored. Reverse transcription-PCR revealed that expression of bla(KPC-3) encoding D179Y/T243M and D179Y variants was diminished compared to bla(KPC-3) expression in baseline isolates. In conclusion, the development of resistance-conferring bla(KPC-3) mutations in K. pneumoniae within 10 to 19 days of ceftazidime-avibactam exposure is troubling, but clinical impact may be ameliorated if carbapenem susceptibility is restored in certain isolates.